A Chlamydia trachomatis 23S rRNA G1523A variant escaping detection in the Aptima Combo 2 assay (Hologic) was widespread across Denmark in July–September 2019. Issue 6 (4th May 2020) - Hadad, Ronza; Jensen, Jørgen Skov; Westh, Henrik; Grønbæk, Ida; Schwartz, Lasse Jessen; Nielsen, Lene; Vang, Tobias Müller; Nielsen, Rikke; Weinreich, Lenette Sandborg; Skov, Marianne N.; Olsen, Marlene; Møller, Jens Kjølseth; et al.
Abstract : Chlamydia trachomatis infection is the most common bacterial sexually transmitted infection globally, and nucleic acid amplification tests (NAATs) are recommended for highly sensitive and specific diagnosis. In early 2019, the Finnish new variant of Chlamydia trachomatis (FI‐nvCT) was identified. The FI‐nvCT has a C1515T mutation in the 23S rRNA gene, making it escaping detection in the Aptima Combo 2 (AC2; Hologic) NAAT, and the FI‐nvCT has been subsequently reported in Sweden and Norway. In the present study, we investigated the presence of the FI‐nvCT and other AC2 diagnostic‐escape CT mutants in July–September 2019 in Denmark. The FI‐nvCT was present but rare in Denmark. However, another AC2 diagnostic‐escape CT mutant (with a 23S rRNA G1523A mutation) was found to be widespread across Denmark, accounting for 95% (76/80) of AC2 diagnostic‐escape nvCT samples from five Danish CT‐diagnostic laboratories. This nvCT‐G1523A has previously only been detected in one single sample in the United Kingdom and Norway, respectively. It is vital to monitor the continued stability of the NAAT targets in local, national and international settings and monitor as well as appropriately analyse incidence, unexplained shifts in diagnostics rates and/or annual collections of samples diagnosed as negative/equivocal using NAATs with different target(s). Furthermore, diagnostic CT NAATs with dual target sequences are crucial, and fortunately, an updated Hologic AC2 assay including one additional target sequence is in advanced development.